OVERVIEW OF KNOWLEDGE ABOUT OBESITY IN STUDENTS OF THE FACULTY OF MEDICINE, UNIVERSITY OF TARUMANAGARA - Nugraha, Liem Kandi; Yapri, Julius Chandra (UNG, 2026)
In recent years, there has been an increase in obesity cases in Indonesia, with obesity rates in adults rising steadily between 2013 and 2018. This situation is concerning because obesity contributes to various degenerative diseases that may reduce population productivity. Factors such as limited nutritional education and the widespread promotion of unhealthy foods through social media can influence public understanding of obesity. Despite this growing issue, evidence related to obesity knowledge among medical students in Indonesia remains limited, particularly regarding how well pre-clinical students understand definitions, risk factors, and management strategies for obesity.Therefore, this study was conducted to determine the level of knowledge about obesity among Tarumanagara University medical students. A questionnaire consisting of statements related to the definition, risk factors, and treatment of obesity was administered, and the distribution of respondents’ answers was analyzed to illustrate their level of understanding. From research conducted on 103 seventh-semester students, it was found that 8.7% had good knowledge and 57.3% had sufficient knowledge. The study provides a novel contribution by presenting institution-specific data that fills a gap in national evidence regarding obesity knowledge among Indonesian medical students, especially those in the transitional phase from pre-clinical to clinical training—an area that has rarely been explored in previous studies. The findings highlight the need for strengthening obesity-related education in medical curricula. The author suggests incorporating additional items that reflect both formal and informal factors affecting obesity to provide a more comprehensive understanding among future health professionals.